APPLICATION OF ARTIFICIAL INTELLIGENCE IN DIGITAL INFORMATION TECHNOLOGIES AND PROGRAMMING DISCIPLINES IN HIGHER EDUCATIONAL INSTITUTIONS - Dilmurodovich, Khudoyberdiev Abdumalik (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: The application of artificial intelligence and digital technologies in the educational process is becoming one of the main directions of the modern education system. This document discusses the technologies for using artificial intelligence in teaching programming, their integration into the educational process, as well as tools that increase efficiency for students. Method: First of all, it is emphasized that artificial intelligence platforms for automating code writing, such as GitHub Copilot or ChatGPT, serve to create an easy and fast programming environment for students. The importance of project management tools in developing students' teamwork skills in education is considered. The process of creating machine learning models using AI and applying them to solve practical problems is also covered in detail. Results: It is noted that the role of AI technologies is strong in making the educational process interactive, personalized and innovative. Novelty: The document presents modern resources, platforms, software tools and scientific sources recommended for students. This annotation helps to understand the role of artificial intelligence in teaching digital technologies and programming.